1992
DOI: 10.1557/jmr.1992.2219
|View full text |Cite
|
Sign up to set email alerts
|

Solid solutions in the system Ag2S–Ag2Se

Abstract: Optical, electron microprobe, and x-ray diffraction analysis of 88 samples of various compositions between Ag2S and Ag2Se synthesized at high temperature in sealed quartz tubing indicates the presence of two solid-solution series in this system at ambient (room) conditions. One series extends from Ag2S to approximately Ag2S0.4Se0.7 and has the Ag2S-III-type structure (monoclinic). The second series ranges from Ag2S0.3Se0.7 to Ag2Se and is characterized by the Ag2Se-II-type structure (orthorhombic). Members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
2
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 12 publications
3
26
2
8
Order By: Relevance
“…The transition temperature decreases from 263 to 173 K in the range 0 ≤ x ≤ 0.3, whereas it increases from 171 to 323 K in the range 0.62 ≤ x ≤ 1. This behaviour of decrease in transition temperatures away from the two pure end-member compositions closely resembles that found in the system Ag 2 S-Ag 2 Se by Pingitore et al [7,8]. The occurrence of thermal minima could be explained as follows.…”
Section: Phase Transition Of Agsupporting
confidence: 85%
“…The transition temperature decreases from 263 to 173 K in the range 0 ≤ x ≤ 0.3, whereas it increases from 171 to 323 K in the range 0.62 ≤ x ≤ 1. This behaviour of decrease in transition temperatures away from the two pure end-member compositions closely resembles that found in the system Ag 2 S-Ag 2 Se by Pingitore et al [7,8]. The occurrence of thermal minima could be explained as follows.…”
Section: Phase Transition Of Agsupporting
confidence: 85%
“…The Ag 2 SAg 2 Se chalcogenides are characterized by the presence of phase transitions and structure phase transformations [1][2][3][4][5]. Roy et al [6] suggested using silver sulfide and selenide transitions as geologic thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al [6] suggested using silver sulfide and selenide transitions as geologic thermometers. The low temperature forms of Ag 2 S and Ag 2 Se are intrinsic semiconductors, the high temperature allotropes are conductors [2,3]. Ag 2 S, Ag 4 SSe and Ag 2 Se have recently attracted considerable attention due to their optical, electrical, and thermoelectric properties [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations